Effect of Zig-Zag Run Training on the Basketball Dribbling Skills of Kepahiang Porprov Athletes - Anggara, Deffri; Personi, Megi; Putra, Dwingki Marta (Hanoman Journal: Physical Education and Sport, 2023)
Purpose of this research is to determine the effect of Zig-Zag Run training on the basketball dribbling skills of Kepahiang Porprov athletes. The method used in this research. The aim of this research is to determine the effect of Zig-Zag Run training on the basketball dribbling skills of Kepahiang Porprov athletes. So this research is a quasi-experimental type. The experimental method can be said to be a method used to look for certain influences on others under controlled conditions. Based on research results, it was found that the basketball dribbling skills of Kepahiang Porprov athletes increased after being given zig-zag run training, which can be seen from the results of the pre-test average, namely 19, after being given zig-zag run training it increased to 30. This proves that Agility training is very helpful for improving an athlete's dribbling skills. Meanwhile, for the group that was not given zig-zag run training, but still did the usual training, the increase was only slight, with an average of 23.